2013
DOI: 10.1007/s11657-013-0155-y
|View full text |Cite
|
Sign up to set email alerts
|

Concern and risk perception of osteoporosis and fracture among post-menopausal Australian women: results from the Global Longitudinal Study of Osteoporosis in Women (GLOW) cohort

Abstract: Women's concern and risk perception of osteoporosis and osteoporotic fractures were reasonably well founded. However, increasing age, height loss, smoking and drinking were not associated with concern and perception despite being known osteoporosis risk factors. These factors should be considered in planning for education and awareness raising programmes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 23 publications
0
15
0
3
Order By: Relevance
“…One of the risk factors mentioned by National Osteoporosis Foundation in its guidelines for MENA region (Middle East and North Africa) is having personal history of fractures as an adult [8]. Fractures occurring during adulthood on exposure to some exercise, weight lifting or falls indicate weak bones and low bone mass density [18] and are a concern for future risk of osteoporosis [19]. Hence fractures and low bone density follow a viscous cycle; one leading to other and aggravating the condition further.…”
Section: Discussionmentioning
confidence: 99%
“…One of the risk factors mentioned by National Osteoporosis Foundation in its guidelines for MENA region (Middle East and North Africa) is having personal history of fractures as an adult [8]. Fractures occurring during adulthood on exposure to some exercise, weight lifting or falls indicate weak bones and low bone mass density [18] and are a concern for future risk of osteoporosis [19]. Hence fractures and low bone density follow a viscous cycle; one leading to other and aggravating the condition further.…”
Section: Discussionmentioning
confidence: 99%
“…Details of the study were described previously [12, 21]. In Australia, a convenience sample of 8,029 eligible female patients was identified through 51 general practitioners from 14 practices around Sydney, between January 2007 and February 2008.…”
Section: Methodsmentioning
confidence: 99%
“…However, the study showed that factors such as height loss, aging, smoking, and drinking were not among the factors that caused concern among participants. 12 …”
Section: Discussionmentioning
confidence: 99%